Biodegradation of Deoxynivalenol by a Novel Microbial Consortium - Wang, Yanxia; Wang, Gang; Dai, Yijun; Wang, Yu; Lee, Yin-Won; Shi, Jianrong; Xu, Jianhong (Frontiers in Microbiology, 2020)
Deoxynivalenol (DON), a common mycotoxin of type B trichothecene, is produced mainly by several Fusarium species. DON causes great losses in farming and poses severe safety risks to human and animal health. Thus, DON contamination in cereals and DON toxicity are of worldwide concern. In this study, we screened the bacterial consortium C20, which efficiently degraded almost 70 μg mL-1 DON within 5 days. The bacterial consortium also had the ability to degrade 15-acetyl-DON, 3-acetyl-DON and T-2 toxin. The bacterial consortium C20 was able to degrade DON under a wide range of pH and temperature conditions. The optimal temperature and pH for DON degradation were 30°C and pH 8.0, respectively. The bacterial consortium C20 comprised different bacterial genera, and several strains were found to significantly increase when cultured in Mineral Medium with 100 μg mL-1 DON based on the analysis of the sequences of the hypervariable V3-V4 region of the 16S rRNA gene. 3-keto-DON was confirmed as a degradation product of DON by liquid chromatography/time-of-flight/mass spectrometry (LC-TOF-MS) and nuclear magnetic resonance (NMR) analyses. The results indicated that the bacterial consortium C20 is a potential candidate for the biodegradation of DON in a safe and environmentally friendly manner.